EFFECTIVENESS OF TEXT MESSAGE INTERVENTION TO IMPROVE KNOWLEDGE, ATTITUDES AND PRACTICES OF PARENTS IN DENTAL HEALTH CARE FOR 3-YEAR-OLD CHILDREN AT SOME PRESCHOOLS IN HA NAM PROVINCE (Vietnam Journal of Community Medicine, 2022)
This study was conducted to evaluate the effectiveness of interventions using mobile messages to improve knowledge, attitudes and practices of parents in dental health care for 3-year-old children at some preschools in Ha Nam province. The before-after controlled trial was conducted on 430 parents of 3-year-old children at 4 preschools in Phu Ly city, Ha Nam province. The difference in difference evaluation approach was applied. Results show that, compared with the control group, the intervention could help to increase 3.57 times the likelihood of having good knowledge at 6 months after the intervention, 3.46 times the probability of having a good attitude after 6 months, and 2.84 times the probability of having good practices after 12 months. Results showed the feasibility and acceptability of implementing these interventions to the population to prevent early tooth decay in children.
Keywords: Knowledge, attitude, practice, text message, children.